2020
DOI: 10.1093/cid/ciaa1894
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Effectiveness of an All-Oral, Bedaquiline-Based, Shorter Treatment Regimen for Rifampicin-Resistant Tuberculosis in High Human Immunodeficiency Virus (HIV) Burden Rural South Africa: A Retrospective Cohort Analysis

Abstract: Background At the end of 2018, South Africa updated its all-oral regimen, to include bedaquiline (BDQ) and two months of linezolid (LZD) for all patients initiating the shorter 9 to 12 months regimen for rifampicin-resistant tuberculosis (RR-TB). We assessed a group of patients in rural KwaZulu-Natal for safety and effectiveness of this treatment regimen under programmatic conditions. Methods We conducted a retrospective coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 19 publications
1
22
0
5
Order By: Relevance
“…In critically ill COVID-19 patients who are unable to tolerate diagnostic bronchoscopy, compatible clinical and radiological features with elevated serum biomarkers levels of LDH and BDG may be the only useful tools to warrant an empirical trial of anti-PJP therapy such as sulfamethoxazole-trimethoprim (SMX-TMP) [ 59 ]. BDG levels are typically low, less than the cut-off of 80 pg/mL in COVID-19 infection, as the COVID-19 virus lacks the polysaccharide cell walls present in certain fungal and bacteria microorganisms [ 60 , 61 ]. In 2011, a meta-analysis demonstrated that serum BDG had 94.8% sensitivity and 86.3% specificity for the diagnosis of PJP in the setting of compatible clinical manifestations and risk factors [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…In critically ill COVID-19 patients who are unable to tolerate diagnostic bronchoscopy, compatible clinical and radiological features with elevated serum biomarkers levels of LDH and BDG may be the only useful tools to warrant an empirical trial of anti-PJP therapy such as sulfamethoxazole-trimethoprim (SMX-TMP) [ 59 ]. BDG levels are typically low, less than the cut-off of 80 pg/mL in COVID-19 infection, as the COVID-19 virus lacks the polysaccharide cell walls present in certain fungal and bacteria microorganisms [ 60 , 61 ]. In 2011, a meta-analysis demonstrated that serum BDG had 94.8% sensitivity and 86.3% specificity for the diagnosis of PJP in the setting of compatible clinical manifestations and risk factors [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…The odds of death within 30 days of ICU admission increased 1.41-fold (1.10–1.81; p = 0.007) for each point increase in the initial BAL GM index [ 19 ]. In the study of White et al, all-cause mortality rates ranged from 46.7% (95% CI 24.8–69.9) in CAPA patients receiving appropriate antifungal therapy to 100% (95% CI 51.1–100) in patients not receiving appropriate antifungal therapy [ 20 ]. Van Biesen et al found a mortality of 22.2% in patients with CAPA based on NBL and 15.1% in patients without CAPA [ 42 ].…”
Section: Key Questionsmentioning
confidence: 99%
“…This finding is consistent with a meta-analysis 22 that established that the use of injectable agents was associated with higher mortality among patients with rifampicin-resistant tuberculosis and other meta-analyses 22 , 23 that suggested bedaquiline has the potential to achieve a higher sputum culture conversion rate and a lower mortality risk among patients with rifampicin-resistant tuberculosis compared with patients not receiving bedaquiline. A study by Tack and colleagues 24 suggests an all-oral, bedaquiline-based regimen that includes linezolid is safe and effective; however, the study was not comparative and it remains to be elucidated if such a regimen would be superior to the bedaquiline-containing regimen (without linezolid) in this analysis.…”
Section: Discussionmentioning
confidence: 90%